1978
DOI: 10.1159/000158160
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cells in the Development of Plasmatic Arterionecrosis, Arteriosclerosis, and Arterial Contraction

Abstract: Plasmatic arterionecrosis, the causative lesion of hypertensive cerebral hemorrhage, follows upon medial muscle cell necrosis. The development of medial muscle cell necrosis, the earliest cerebral arterial change seen in hypertensive rats, was inhibited when these animals were fed a cholesterol and lard-supplemented diet. Insudation of fibrin was noted in the arterial intima of hypertensive rats with bilaterally constricted renal arteries. Removal of the constriction induced a fall in the elevated blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 2 publications
(2 reference statements)
1
41
1
Order By: Relevance
“…4) Cholesterol may be important for maintaining the integrity of small blood vessels and their resistance to rupture. 18) The present study found that use of edaravone increased hemorrhagic transformation, but identified no significant relationship between outcome and use of edaravone. Except for patients with parenchymal hematoma-1 and -2, the rate of good outcomes was higher in the edaravone group than in the non-edaravone group.…”
Section: Discussioncontrasting
confidence: 73%
“…4) Cholesterol may be important for maintaining the integrity of small blood vessels and their resistance to rupture. 18) The present study found that use of edaravone increased hemorrhagic transformation, but identified no significant relationship between outcome and use of edaravone. Except for patients with parenchymal hematoma-1 and -2, the rate of good outcomes was higher in the edaravone group than in the non-edaravone group.…”
Section: Discussioncontrasting
confidence: 73%
“…A significant increase in glycerol permeability and osmotic fragility was demonstrated in cholesterol-depleted/reduced cell membranes and erythrocytes.38,39 Our case-control study showed that both serum cholesterol and the cholesterol content of red cell membranes were significantly lower among cerebral hemorrhage cases than for noncases, and osmotic fragility of erythrocytes was significantly greater.40 Experimental studies indicated that a rise in serum total cholesterol associated with diet in animals attenuates the development of angionecrosis in intracerebral arteries and stroke. 41,42 Therefore, we infer that the significant and consistent fall in the incidence of hemorrhage across all age-sex groups could be attributed to the combination of the population TC rise and blood pressure fall. However, potential confounding factors such as relative protein deficiency and alcohol consumption are not excluded.…”
Section: Determination Of Risk Factors For Strokementioning
confidence: 87%
“…The participation rates were high (between 74% and 92%) for all age-sex groups in three surveys except men ages [40][41][42][43][44][45][46][47][48][49] in the 1980-1983 survey (64%), who gained another opportunity for health examination at their worksites. The effect of bias due to this lower rate may be small because strong and consistent trends of most risk characteristics were seen across all age-sex groups.…”
Section: Methodsmentioning
confidence: 99%
“…The earliest cerebral arterial change seen in hypertensive rats was inhibited when these animals were fed a cholesterol and lard-supplemented diet. 31 Other previous studies suggested that the membrane characteristics in stroke-prone spontaneously hypertensive rats depended partially on the amount of cholesterol in which was significantly decreased in stroke-prone spontaneously hypertensive rats and the erythrocytes from the group with a family history of stroke were more labile than those with no family history of stroke. 32 Low serum cholesterol may suggest the existence of malnutrition and is often found associated with a low level of plasma albumin.…”
Section: Study Limitationsmentioning
confidence: 93%